Fourth-Year Baccalaureate Nursing Students' Perceptions of Inclusive Learning Environments - Metzger, Maureen; Taggart, Jessica; Aviles, Emerson (The Journal of nursing education, 2020)
Creating inclusive learning environments is a priority in nursing education, yet faculty are hindered by a dearth of evidence-based inclusive pedagogical strategies. In addition, little is known about students' perceptions of inclusive learning environments. Fourth-year baccalaureate nursing students from majority and underrepresented minority groups (n = 13) participated in focus groups at two time points across the academic year. Discussion topics included pedagogical strategies most strongly associated with inclusivity, facilitators and barriers to inclusivity, outcomes of inclusive learning experiences, and recommendations for promoting inclusivity in education and nursing practice. Qualitative content analysis resulted in three themes: 1) underrepresented minority and majority groups described inclusive learning environments differently, 2) every aspect of the learning community affects inclusivity but teachers are especially influential, and 3) the outcomes of an inclusive learning environment extend beyond the classroom. These findings may help create inclusive learning environments that support diversity and inclusive excellence in nursing education. [J Nurs Educ. 2020;59(5):256-262.].